Synthesis, FT-IR and NMR Characterization, Antibacterial and Antioxidant Activities, and DNA Docking Analysis of a New Vanillin-Derived imine Compound - Çelik, Sefa; Özkök, Funda; Özel, Ayşen E.; Çakır, Elif; AKYÜZ, SEVİM (Elsevier, 2021)
A new vanillin-derived imine compound, [5-((1E,15E)-16-(3-methoxy-4-hydroxyphenyl)hexadeca-1',15'-diimine)-2-methoxyphenol], was synthesized and characterized by DFT calculations, experimental and theoretical vibrational spectroscopy and NMR techniques. The most stable molecular structure of the title compound has been calculated by optimizing the molecular structures using DFT/B3LYP/6-311+G(d,p) level of theory. The fundamental vibrational wavenumbers, IR and Raman intensities for the optimized geometry of the compound under investigation were determined and compared to the experimental vibrational spectra. The vibration assignment of the molecule was made in accord with the potential energy distribution (PED) of the vibration modes and using the group frequencies. The molecular electrostatic potential (MEP), HOMO and LUMO orbitals were also calculated. The antibacterial activities of the new vanillin-derived imine compound against gram-positive and gram-negative bacteria was determined. The antioxidant activity of the title compound was also examined. Moreover, the molecular docking studies have been performed to understand the nature of binding of the compound with DNA. The results indicated that the investigated compound has a good binding affinity with DNA and interacted with the DG4 and DT7 residues via the intermolecular hydrogen bonds.
Keywords: Vanillin; Antioxidant; DFT Calculations; Molecular Docking; Vibrational Analysis